Efficacy of an Integrated Simulation-Based Education Approach to Train Non-Technical Skills in Medical Undergraduate Students - Parisa Moll-Khosrawi; Josephine Küllmei; Christian Zöllner; Leonie Schulte-Uentrop (MDPI AG, 2023)
Introduction: Non-technical skills (NTS) are essential to maintain best patient care and to enhance patient safety. Therefore, the early integration and implementation of non-technical skills (NTS) training during undergraduate medical education has not only been repeatedly emphasized but is crucial to ensure patient safety. However, there is a gap in knowledge on how to effectively convey and thereby enhance NTS in under- or postgraduate medical training. Although medical educators are eager to convey NTS, the best approach to do so is yet to be found. Next to didactic and teaching approaches, the design of the curriculum, in the sense of an integrated curricula, might have an influence in conveying NTS effectively. Therefore, we investigated if repetitive simulation-based training enhanced the NTS of medical undergraduates. Methods: 945 undergraduate students in their 1st, 2nd, 3rd and 4th year of medical studies who attended mandatory emergency simulation trainings at the medical faculty in Hamburg participated in this prospective observational study. The trainings are designed to align to a learning spiral (vertically integrated curriculum) and build upon each other, resulting in repetitive and advanced training. Each training has a preset training-specific standardized simulation scenarios. To determine progress in NTS performance, the NTS of the students were assessed during each training with the Anaesthesiology Students' NTS (AS-NTS) taxonomy, which is composed of three dimensions. Differences in performance between the investigated cohorts of students were calculated with an analysis of variance (Welch's ANOVA) and with a follow-up post hoc test (Games-Howell), and the significant differences were analysed. Results: The NTS of the undergraduate students improved with every ascending training and, hence, year of medical school. The overall NTS performance of the 4thyear undergraduate students differed significantly compared to the 1st, 2nd and 3rd year undergraduate students performances, F = 6.72 (4, 439.6), p ≤ 0.001. The greatest improvement was detected on dimension one of the AS-NTS ("Planning tasks, prioritising and problem-solving") (F = 6.75 (4, 434.5), p ≤ 0.001), where 4th year undergraduates performed at a significantly higher skill level than the 1st, 2nd and 3rd year undergraduate students. On dimension two ("Teamwork and Leadership") and three ("Team orientation"), significant differences were pronounced between the 4th year and 1st year undergraduate students (F = 3.56 (4, 442.9), p = 0.010; F = 4.50 (4, 441.0), p = 0.001). The lowest skill improvement was observed on dimension two. Conclusions: NTS are essential skills to complement technical skills and hereby ensure patient safety. The early longitudinal and vertical integration of NTS training in undergraduate medical curricula (learning spiral) is an effective approach to enhance and foster the NTS of future doctors.